Energetic and exergetic analysis of a domestic refrigerator system with LPG as a replacement for R134a refrigerant, using POE lubricant and mineral oil based TiO2-, SiO2- and Al2O3-lubricants. (July 2018) - Gill, Jatinder; Singh, Jagdev; Ohunakin, Olayinka S.; Adelekan, Damola S.
Highlights: Energetic and exergetic performance analysis with R134a and LPG refrigerants and different lubricants was carried out. Energetic and exergetic performance parameters with LPG /Nano-lubricants found better than R134a/POE. Nano-lubricant based on TiO2 was chosen as the optimal Nano-lubricant in this study. Compressor discharge temperature was the lowest for LPG refrigerant using SiO2 based nano-lubricant. Abstract: This paper experimentally investigated energetic and exergetic performance analysis of a domestic refrigerator using R134a and LPG refrigerants with different lubricants (polyol-ester (POE), mineral oil (MO), and TiO2, SiO2, Al2 O3 nanoparticles dispersed in mineral oil).The energetic and exergetic performance analysis of the domestic refrigerator were investigated with test parameters including compressor power consumption, cooling capacity, coefficient of performance (COP), discharge temperature, irreversibility in the components, total irreversibility and second law efficiency. Findings showed that the lowest compressor power consumption and total irreversibility were observed in refrigerator with 40 g charge of LPG/TiO2 -MO lubricant (0.2 g/L of TiO2 ); these values of compressor power consumption and total irreversibility were 15.87% and 31.69%, respectively, lower than for R134a/POE lubricant. In addition, the domestic refrigerator using LPG refrigerant at 40 g charge with TiO2 -MO (0.2 g/L TiO2 ) lubricant, had the highest COP and second law efficiency among the selected nano-lubricants. These values of COP and second law efficiency were 56.32% and 47.06%, respectively, higher than that of R134a/POE. Futhermore, compressor discharge temperature of the domestic refrigerator with 40 g charge of LPG/TiO2 -MO lubricant (0.2 g/L of TiO2 ) was found to be lower than that of R134a/POE. Hence, extended compressor life may be expected with the adoption of TiO2 -Mineral oil lubricant. It can be concluded that based on energetic and exergetic performance analysis, the domestic refrigerator using the 40 g charge of LPG/TiO2 -MO (0.2 g/L TiO2 ) performed better than R134a/POE.